2008
DOI: 10.1007/s11218-008-9066-y
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and victimisation in school children: the role of social identity, problem-solving style, and family and school context

Abstract: The relationship between social identity, family and school context, problem-solving style, self-esteem, health behaviour, psychological distress, and victimisation, was explored in a quasi-experimental survey of 461 children aged between 11 and 15 years old. There was a high prevalence of victimisation (29%) in the group and 44% of those victimised scored above the clinical cut-off on the GHQ. Victims exhibited higher levels of psychological distress, lower self-esteem, more unhealthy behaviours, less support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
3
25

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 44 publications
5
56
3
25
Order By: Relevance
“…Documented prevalence rates for bullying vary greatly across studies, with 10% to 33% of students reporting victimization by peers, and 5% to 13% admitting to bullying others (e.g., Cassidy, 2009;Dulmus, Sowers, & Theriot, 2006;Kessel Schneider, O'Donnell, Stueve, & Coulter, 2012;Nansel et al, 2001;Perkins, Craig, & Perkins, 2011;Peskin, Tortolero, & Markham, 2006). Such variations reflect differences in assessment approaches, as well as differences across individuals (sex, age), contexts, and cultures.…”
Section: How Prevalent Is Bullying and Victimization?mentioning
confidence: 99%
“…Documented prevalence rates for bullying vary greatly across studies, with 10% to 33% of students reporting victimization by peers, and 5% to 13% admitting to bullying others (e.g., Cassidy, 2009;Dulmus, Sowers, & Theriot, 2006;Kessel Schneider, O'Donnell, Stueve, & Coulter, 2012;Nansel et al, 2001;Perkins, Craig, & Perkins, 2011;Peskin, Tortolero, & Markham, 2006). Such variations reflect differences in assessment approaches, as well as differences across individuals (sex, age), contexts, and cultures.…”
Section: How Prevalent Is Bullying and Victimization?mentioning
confidence: 99%
“…In a British study, it was found that direct verbal aggression was the most common form of bullying [17]. According to [18], bully victims had higher levels of psychological distress, low self-esteem, more unhealthy behaviors and less support from parents and teachers. Additionally, the male students seem to be more often involved in aggressive communication as assailant or victim [19].…”
Section: Introductionmentioning
confidence: 99%
“…Victims of bullying are more likely than other students to report mental health disorders [5,6] and emotional distress [7] and to engage in unhealthy behaviours such as smoking, drinking, and drug use [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of factors contributing to peer victimization have been identified in the literature, including reporting negative school experiences [8] such as social marginalization at school [7,9], not being accepted by peers [10], being teased for being overweight or obese [11], and exhibiting low self-esteem [5,[12][13][14]. Family socioeconomic standing and relations have also been found to play a role in bullying-victimization.…”
Section: Introductionmentioning
confidence: 99%